Respuesta :

Answer:

[tex]\left \{ {{x=5} \atop {y=7}} \right.[/tex]

Step-by-step explanation:

[tex]\left \{ {{x+y=12} \atop {3y = 4x+1}} \right.[/tex]

[tex]\left \{ {{x=12-y} \atop {3y=4x+1}} \right.[/tex]

We are going to do a replacement of x for a second equation

So instead

[tex]3y=4x+1[/tex]

in the place of x we are putting 12-y from the first equation, so

[tex]3y = 4(12-y)+1[/tex]

To leave the brackets we need to do multiplication

[tex]3y = 4*12-4*y+1[/tex]

Which is

[tex]3y = 48-4y+1[/tex]

[tex]3y = -4y+49 /+4y\\7y = 49 /:7\\y = 7[/tex]

How to determine x? From the first equation:

If the x +y = 12 then the x = 12-y so x = 12-7 = 5

We should write solution as a pair:

[tex]\left \{ {{x=5} \atop {y=7}} \right.[/tex]